Non-Sequential Linear Construction Project Scheduling Model for Minimizing Idle Equipment Using Constraint Programming (CP) - Shu-Shun Liu; Agung Budiwirawan; Muhammad Faizal Ardhiansyah Arifin (Mathematics, 2021)
Over the last several decades, the scheduling of linear construction projects (LCPs) has been explored extensively by experts. The linear scheduling method (LSM), which focuses on work rate and work continuity, has the advantage of tackling LCPs’ scheduling problems. The traditional LSM uses work continuity to monitor resource allocation continuity on the premise that activities with the same type of work use the same crew. However, some LCPs require a combination of different types of equipment to comprise the crew. Sometimes, parts of different crews require the same types of equipment, and sometimes, the same crew requires different equipment configurations. This causes the pattern of work continuity to be different from the pattern of resource allocation continuity. Therefore, we propose an optimization model of the LSM to minimize idle equipment on a non-sequential linear construction project—i.e., a road network maintenance project. This model is intended to minimize the number of idle equipment and their idle time to achieve more efficient scheduling for linear construction projects. This model offers novel details of resource allocation continuity assessment by taking into account equipment combination and configuration (ECC). Therefore, the scheduling concept used by the proposed model is named the linear scheduling model with ECC (LSM–ECC). The model was developed using constraint programming (CP), as CP has good performance and robustness in the optimization field. The model was implemented to a representation of a road network maintenance project and has satisfactory results.